Health Level of PT Bank Perkreditan Rakyat Duta Perdana Using CAMELS Method Period 2016-2020 - Eddy, Pujiono; Dinda, Meivina; Irman, Mimelientesa; Purnama, Intan; Estu, Ahmad Zulkarnain (Luxury: Landscape of Business Administration, 2023)
This study aims to analyze the health level of the PT. Bank Perkreditan Rakyat (BPR) Duta Perdana Pekanbaru of 2016-2020 period using the CAMELS method. The data analysis technique used logistic regression testing on financial ratios. The value of CAR (Capital Adequacy Ratio) at BPR Duta Perdana Pekanbaru during 2016-2020 was 3.39, namely in the fourth quarter of 2016, it shows the level of health in terms of a low asset adequacy ratio but still meets the minimum requirements of Bank Indonesia regulations. The research shows that the health level assessment using the CAMELS method from PT. Bank Perkreditan Rakyat BPR) Duta Perdana Pekanbaru is in the unhealthy category.